Pengembangan Game Puzzle Find Grass Menggunakan Algoritma Backtracking - Yulyanto; Tito Sugiharto; Fikri Maudia Arsyad (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Game like a tools of entertainment that is enjoyed and played by many grups ranging from children. teenagers and adults. With the rapid development of technology, games are becoming more practical. For example, nowadays we no need to buy a games console like Playstation to play a games. One of the games that has a good impact to users is a game in the form of education, from the explanation above, idea arises to take research to make a game entitled “Find Grass” based on 3D perspective android. That the concept of each level of the game, user must direct or control the player, namely a rabbit looking for a grass to get to the final destination poin with limited time. In making this game requires a Backtracking Algorithm that can find the fastest path to get to a certain destination poin and later will be applied to the help system in the game. The system development method is GDLC (Game Development Life Cycle) which has stages such as initiation, pre-production , production, beta, release. For application design using UML (Unified Modeling Language ). In addition , the application to create games uses Unity 3D. The final result of the application created is a game that is compatible on smartphone devices with an android operating system at least 5.0 (Lollipop). This game has several menus including the main menu, stage menu consisting of 3 stage guide menu and exit menu.